Germination Characteristics Is More Associated With Phylogeny-Related Traits of Species in a Salinized Grassland of Northeastern China - Zhao, Ming; Liu, Zhaogang; Zhang, Hongxiang; Wang, Yuanyuan; Yan, Hong (Frontiers in Ecology and Evolution, 2021)
Knowing the determinants of seed germination helps us understand plant adaptive strategies to the environment and predict population and community regeneration under climate change. However, multiple factors, including plant and seed traits that influence germination and their relative importance, have received little attention. Here, seed germination experiments were conducted on newly collected seeds for 89 herbaceous species from salinized Songnen grassland. We tested the effects of multiple phylogeny-related plant traits and seed morphological and physiological traits on germination percentage and initial germination time and their relative contribution to shaping germination variation. We found that biennials had higher germination percentages and rates than annuals and perennials. Species with brown seeds had higher germination percentages than those with yellow and black seeds. Eudicots germinated faster than monocots, and seeds with morphophysiological dormancy required more time to initiate germination than those with other kinds of dormancy. Phylogeny-related factors explained more of the variation in germination than seed traits. Seed mass and volume of the large-seeded, but not small-seeded group species were positively correlated with germination percentage. Our findings provide important information for understanding germination variation across species and local adaptation for species in the salinized Songnen grassland.